"These patients look lost" – Community pharmacy staff's identification and support of patients with limited health literacy. (4th May 2016) - Koster, Ellen S.; Philbert, Daphne; Blom, Lyda; Bouvy, Marcel L.
Abstract: Objective: To date, routine use of health literacy assessment in clinical settings is limited. The objective of this study was to explore if community pharmacy staff can identify patients with limited health literacy, how they identify patients and how they support patients to improve medication use. In addition, perceived barriers in providing care for patients with limited health literacy were assessed. Methods: Structured face‐to‐face interviews with pharmacy staff were performed in 27 community pharmacies. Questions concerned pharmacy staff's experiences with limited health literacy during their work, e.g. recognition of patients, communication strategies and possible interventions for this patient group to improve medication use. Key findings: Results from 74 interviews were included for analysis. Sixty‐eight interviewees (92%) mentioned to identify patients with limited health literacy during their work, mostly based on intuition. Suggested strategies to improve medication use included tailored education and information, intensive support or use of aids such as a multidose drug dispensing system. Pharmacy staff indicated lack of time as a barrier to provide tailored pharmaceutical care. Conclusions: Most participants mentioned to recognize patients with limited health literacy merely on intuition or based on certain patient characteristics. Thus, an unknown number of patients with limited health literacy might be missed. This underlines the need to create more awareness of health literacy among pharmacy professionals. Moreover, training of pharmacy staff and use of aids to identify limited health literacy may help to identify more patients who need additional counselling.